Early changes of peripheral circulating immune subsets induced by PD-1 inhibitors in patients with advanced malignant melanoma and non-small cell lung cancer - Borilova, Simona; Grell, Peter; Selingerova, Iveta; Gescheidtova, Lenka; Mlnarikova, Marie; Bilek, Ondrej; Lakomy, Radek; Poprach, Alexandr; Podhorec, Jan; Kiss, Igor; Vyzula, Rostislav; Vavrusakova, Barbora; et al. (BMC cancer, 2024)
BACKGROUND: Immune checkpoint inhibitors (ICIs), including those targeting PD-1, are currently used in a wide range of tumors, but only 20-40% of patients achieve clinical benefit. The objective of our study was to find predictive peripheral blood-based biomarkers for ICI treatment. METHODS: In 41 patients with advanced malignant melanoma (MM) and NSCLC treated with PD-1 inhibitors, we analyzed peripheral blood-based immune subsets by flow cytometry before treatment initialization and the second therapy dose. Specifically, we assessed basic blood differential count, overall T cells and their subgroups, B cells, and myeloid-derived suppressor cells (MDSC). In detail, CD4 + and CD8 + T cells were assessed according to their subtypes, such as central memory T cells (TCM), effector memory T cells (TEM), and naïve T cells (TN). Furthermore, we also evaluated the predictive value of CD28 and ICOS/CD278 co-expression on T cells. RESULTS: Patients who achieved disease control on ICIs had a significantly lower baseline proportion of CD4 + TEM (p = 0.013) and tended to have a higher baseline proportion of CD4 + TCM (p = 0.059). ICI therapy-induced increase in Treg count (p = 0.012) and the proportion of CD4 + TN (p = 0.008) and CD28 + ICOS- T cells (p = 0.012) was associated with disease control. Patients with a high baseline proportion of CD4 + TCM and a low baseline proportion of CD4 + TEM showed significantly longer PFS (p = 0.011, HR 2.6 and p ˂ 0.001, HR 0.23, respectively) and longer OS (p = 0.002, HR 3.75 and p ˂ 0.001, HR 0.15, respectively). Before the second dose, the high proportion of CD28 + ICOS- T cells after ICI therapy initiation was significantly associated with prolonged PFS (p = 0.017, HR 2.51) and OS (p = 0.030, HR 2.69). Also, a high Treg count after 2 weeks of ICI treatment was associated with significantly prolonged PFS (p = 0.016, HR 2.33). CONCLUSION: In summary, our findings suggest that CD4 + TEM and TCM baselines and an early increase in the Treg count induced by PD-1 inhibitors and the proportion of CD28 + ICOS- T cells may be useful in predicting the response in NSCLC and MM patients.
Keywords: Male; nádory plic; antigeny CD278; Immune Checkpoint Inhibitors; Carcinoma, Non-Small-Cell Lung; Lung Neoplasms; Adult; Aged; dospělí; mužské pohlaví; senioři; CD8-Positive T-Lymphocytes; antigeny CD28; Melanoma; senioři nad 80 let; CD28 Antigens; lidé; CD8-pozitivní T-lymfocyty; Inducible T-Cell Co-Stimulator Protein; ženské pohlaví; Humans; nemalobuněčný karcinom plic; Aged, 80 and over; inhibitory kontrolních bodů; Programmed Cell Death 1 Receptor; antigeny CD279; Female; melanom; lidé středního věku; Middle Aged